Earnings management preceding management buyout offers - Perry, Susan E.; Williams, Thomas H. (Journal of Accounting and Economics, 1994)
There are frequent expressions of concern in the accounting, economics, and legal literature about managers' conflicting duties and incentives in management buyouts. This study is motivated by a concern about the managerial incentive to reduce reported earnings prior to the announcement of the buyout proposal. Our analysis of a sample of 175 management buyouts during 1981-88 provides evidence of manipulation of discretionary accruals in the predicted direction in the year preceding the public announcement of management's intention to bid for control of the company.